Long‐term response to crizotinib in a 17‐year‐old boy with treatment‐naïve ALK‐positive non‐small‐cell lung cancer. Issue 3 (28th January 2022) - Megaro, Giacomina; Miele, Evelina; Spinelli, Gian Paolo; Alessi, Iside; Del Baldo, Giada; Cozza, Raffaele; Russo, Ida; De Pasquale, Maria Debora; Cefalo, Maria Giuseppina; Tomà, Paolo; Carai, Andrea; Di Ruscio, Valentina; et al.
Abstract: Background: Lung cancer is the leading cause of cancer‐related death. NSCLC accounts for 80–90% of cases. In young patients, adenocarcinoma is the most frequent histotype and 3–7% expresses the rearrangement of ALK oncogene, sensitive to TKIs. Crizotinib is the first ALK inhibitor approved by the FDA. Case: We present a case of a 17‐year‐old male with metastatic treatment‐naïve ALK‐positive adenocarcinoma. He was treated with crizotinib and obtained a prolonged response with PFS of 33 months. Conclusion: Crizotinib can be extremely effective in adolescents with treatment‐naïve ALK‐positive NSCLC but fail to prevent a central nervous system relapse. Resistance mechanisms need to be investigated.